2021
DOI: 10.1371/journal.pone.0252307
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of latent tuberculosis infection among health workers in Afghanistan: A cross-sectional study

Abstract: Background About 26% of the world’s population may have latent tuberculosis infection (LTBI). Health care workers are a high-risk category because of their professional exposure. Methods This cross-sectional study assessed the LTBI burden among health care workers in Afghanistan, a high-TB-burden country. We selected health facilities using a systematic sampling technique and invited all workers at the targeted health facilities to participate. Participants were interviewed about sociodemographic and exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In our study, the prevalence of TB infection among hospital personnel was 26.1%. This rate is lower than the prevalence reported in Afghanistan (47.2%) [ 18 ] and India (30%) [ 19 ], but higher than in Riyadh hospitals (4.9%) [ 20 ] and Turkey (1.7%) [ 21 ]. The prevalence in EMRO member countries in 2021 was 41.78% [ 22 ], while among medical personnel in low- and middle-income countries, it was 54% [ 23 ].…”
Section: Discussionmentioning
confidence: 58%
“…In our study, the prevalence of TB infection among hospital personnel was 26.1%. This rate is lower than the prevalence reported in Afghanistan (47.2%) [ 18 ] and India (30%) [ 19 ], but higher than in Riyadh hospitals (4.9%) [ 20 ] and Turkey (1.7%) [ 21 ]. The prevalence in EMRO member countries in 2021 was 41.78% [ 22 ], while among medical personnel in low- and middle-income countries, it was 54% [ 23 ].…”
Section: Discussionmentioning
confidence: 58%
“…In several localities, studies have reported that population groups such as health professionals, contacts of index TB cases and slaughterhouse workers, are at risk of latent tuberculosis because of the profession or proximity to suspected tuberculosis cases [18] [19] [20] [21] [22]. In this way, our population consisted in exposed to tuberculosis including: 1) household contacts of TB index cases, 2) health care workers (HCWs) and 3) slaughterhouses workers (SWs) who gave their consent to participate to the study.…”
Section: Study Population and Sample Collectionmentioning
confidence: 99%
“…The overall prevalence of LTBI in Afghanistan is unknown, although one study of Afghan healthcare workers found an LTBI rate of 47.2% when using tuberculin skin testing. 5 LTBI is defined as a persistent immunological response to Mycobacterium tuberculosis in the absence of active TB disease. There are several tests available for LTBI, all of which assess the T cell response to M tuberculosis.…”
Section: Introductionmentioning
confidence: 99%